Perceived social support, job stress, and self-efficacy as predictors on employee engagement in Malaysia. - Ngu, Wendy Tang Xi; Chua, Jiaen; Tan, Ricky Wai Hong (2024)
This study explores how perceived social support, job stress, and self-efficacy predict employee engagement among university lecturers in Malaysia. It seeks to answer three questions: whether perceived social support enhances engagement, whether job stress reduces it, and whether self-efficacy positively influences it. These insights aim to deepen the understanding of the factors that affect employee engagement, providing a foundation for further research. The study applied a quantitative research design, and data were collected through purposive and snowball sampling from academic staff aged 30 to 60 across various Malaysian universities. The study utilised G*Power software to calculate the sample size and SPSS version 29 for data analysis. The respondents, representing various ethnic groups, provided 192 valid responses. The study validated that perceived social support positively predicted employee engagement, job stress negatively predicted it, and self-efficacy also positively predicted employee engagement in Malaysia. These findings underscore the importance of fostering supportive environments and enhancing self-efficacy to boost engagement while also recognizing the adverse effects of job stress. The study’s implications suggest that higher education institutions should consider strategies to support employee engagement, in line with Malaysia’s National Transformation 2050 (TN50) goals. However, the study’s limitations, including response bias and the exclusion of external stressors, limited generalisability highlight the need for future research to address these factors and extend the investigation to other sectors.